The challenge in diagnosing and managing heterotopic interstitial pregnancy in natural conception / Noor Azura Noor Mohamad … [et al.] - Noor Mohamad, Noor Azura; Daud, Suzanna; Sun, Ta Thow; Singh Chopra, Darminder; Abdullah, Bahiyah (Universiti Teknologi MARA Cawangan Selangor, 2019)
Heterotopic interstitial pregnancy in natural conception is very rare. Definitive diagnosis is made by systematic pelvic ultrasound. Simultaneous viable conception observed in both intraand extra-uterine is pathognomonic of heterotopic interstitial pregnancy. We report a 34-yearold woman primigravida at 10 weeks’ amenorrhoea who underwent evacuation of retained product of conception for missed miscarriage. Intraoperatively, minimal product of conception was retrieved. Bedside pelvic ultrasound showed cystic mass at right superolateral part of uterine fundus suspicious of interstitial pregnancy. Cornual resection was performed via laparotomy. Histopathological examination showed presence of product of conception and interstitial pregnancy. Serum β-human chorionic gonadotropin dropped from 10,027 IU/l on day one post-ERPC to 210 IU/l at day three post-cornual resection. This case report highlighted the challenge in diagnosing heterotopic interstitial pregnancy conceived naturally. Timely diagnosis may avert dire consequences of massive haemorrhage from ruptured uterine cornua.